(untitled) (American Journal of Islam and Society, 1989)
From the earliest times, South Asia* has been a scene of invasion. It is a long tale of incursion. conquest, settlement, and then assimilation. The Greeks, Sakas, and Eushanas forced their way in as dominant groups and established kingdoms and dynasties, only to be assimilated by what Dr. Spear called "the Hindu sponge." The push by Muslims into the sub-continent was by well-worn routes and to a familiar pattern of conquest and rule, first of Sind and the Punjab, then of the Gangetic Plain, and, finally, of almost the whole of South Asia. Conquest and settlement were not followed by assimilation, however. Muslims retained a separate identity and their numbers, proportionate and absolute, grew until today a quarter of all Muslims in the world are to be found in South Asia. In 1975, they formed some 97 percent of the population of Pakistan, 85 percent of that of Bangladesh, and 13 percent of that of India. But these Muslims come from different roots and origins, they speak different languages, and their understanding and practice of Islam differs according to their educational and social background and to their regional and geographicaJ setting. Many of them are of Arab, Afghan, Mughal and Persian descent, but the majority of them are descendants of South Asian converts to Islam. The spread and expansion of Islam and its acceptance by such large groups of people of a variety of ethnic, historical, and cultural backgrounds and across a range of diverse geographical areas can scarcely be the outcome of any simple uniform process. Conversion to Islam is thus a challenging and absorbing subject for research. Yet it has attracted the attention of scholars only since the last decade of the nineteenth century. What follows does not claim to be more than a pre! iminary and rather hurriedly prepared survey of the main theories about conversion to Islam propounded by Asian and Western scholars. The dearth of source material presents difficulties as "medieval Islam" produced no missionaries, bishops, baptismal rites, or other indicators of conversion that could be conveniently recorded by the Muslim chronicler. Hopefully the subject will be a spur to the detailed review and analysis of sources, modern and medieval, which the subject both deserves and requires ...